Parental Income and Financial Attitude on Financial Management Behavior with Financial Knowledge as a Moderation - Ulandari, Ni Luh Darmasanti Aprilia; Anggriani, Rini; Alpiansah , Restu; Dethan, Stevany Hanalyna; Talidobel, Susilo (Target : Jurnal Manajemen Bisnis, 2025)
Financial management behavior can be implemented to attain a satisfactory standard of living. A person's perspective on saving is influenced by their financial attitude and parental income. Financial knowledge has the potential to influence the relationship between parental income and financial attitude toward financial management behavior. This study aims to examine the influence of parental income and financial attitude on financial management behavior moderated by financial knowledge. The study concentrated on 250 respondents from Generation Z in Mataram City, who were selected through purposive sampling techniques with a data collection method using a questionnaire. The data analysis is conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS 3.0 software. The findings indicated that parental income and financial attitude had a positive and significant effect on financial management behavior. However, financial knowledge has failed to mitigate the relationship between parental income and financial management behavior. Financial knowledge was unable to moderate the relationship between financial attitude and financial management behavior. Thus, the findings highlighted the significance of parental income and financial attitude in influencing financial management behavior in Generation Z. Therefore, the findings enhance the comprehension that parental income and financial attitude significantly influence an individual's future financial status.